Filtragem de Pacotes na Borda da Rede: Uma Análise Comparativa com Foco no Consumo de Energia - Silverio, Arthur Eugenio; Guardia, Hélio Crestana (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.233896, 2023)
Edge Security is concerned with protecting not only the devices connected at the borders of the network, but also the core of the network from the traffic generated at these devices. Threat detection systems analyze the behavior of edge computing devices for potential threats and apply policies as early as possible, before they scale the infrastructure. Many aspects make edge security in edge particularly sensitive due to the low computational capacity of devices and the need to aggressively minimize energy consumption. In this sense, this paper presents the results of a comparative analysis of packet filtering using different operating system hooks in a Linux system, ranging from as close to the interface device to using userspace tools. Besides evaluating the CPU load, it was also measured energy consumption in each case. Analysis shows the importance of packet processing always taking place at the lowest layers of the operating system.